Total antioxidant status in fresh and stored human milk from mothers of term and preterm neonates - Luminiţa Păduraru; Daniela Cristina Dimitriu; Andreea Luciana Avasiloaiei; Mihaela Moscalu; Gabriela Ildiko Zonda; Maria Stamatin (Elsevier, 2018)
Background: Antioxidant defense of the body is assured by both endogenous and exogenous factors comprising several enzymes, vitamins, protein components and derivates and oligoelements. Breast milk has been proven to have important and essential antioxidant composition to prevent and protect against diseases in infancy. The objective of this study was to determine the total antioxidant status (TAS) of human milk and to evaluate the differences between premature milk and term milk at different moments of lactation (colostrum, transitional milk and mature milk). A second objective was to evaluate how TAS varies whether the human milk is refrigerated or frozen. Methods: Pumped human milk samples of the third, seven and 30th day were collected from women who had term deliveries (30 cases) and preterm deliveries (60 cases). Samples were refrigerated (+4 °C) or frozen in domestic conditions (−20 °C) for various durations and TAS was determined using the ABTS® technique with Randox® reagents and compared for the two groups. Results: Higher values were found in term versus preterm fresh milk at 30 days of lactation. A slight reduction in TAS was found after 72 h of refrigeration, while 1 week freezing produced significant decrease of total antioxidants. Freezing for 12 weeks reduced more than 50% of TAS in fresh milk. Conclusion: Breastfeeding provides the optimal antioxidant for neonates, regardless of gestational age. Fresh milk has the higher antioxidant power. When it is not available, refrigerated milk for 24 h is better than for 72 h and preferable than frozen milk. Freezing human milk for 3 months in household conditions markedly diminishes TAS. Key Words: early lactation, human milk, preterm, term, total antioxidant status